Perception of Information Communication Technology (ICT) on Reporting of Educational Management Corruption Among Academic Staff in Public Universities in Anambra State - Gloria, Ikegbusi Njideka; Emmanuella, Awadiegwu Amaka; Stella, Oranusi Ndidi (International Journal of Applied and Advanced Multidisciplinary Research, 2024)
This study explored the role of Information Communication Technology (ICT) in shaping academic staff’s awareness, perception, and willingness to report corrupt practices within the management structures of public universities in Anambra State. The core aim was to assess how the adoption of ICT tools and platforms influences the transparency of educational management and the reporting behaviour of staff. The findings demonstrated that the effective utilization of ICT significantly enhances perceptions of transparency in educational management and increases the likelihood of reporting corrupt practices among academic staff. The study concluded that integrating ICT into university management processes is essential for promoting accountability and curbing corruption. It recommended that universities should implement comprehensive training programs on the use of ICT for anti-corruption efforts. These training sessions should focus on increasing the digital literacy of academic staff, providing them with the necessary skills to identify, report, and discuss corrupt practices through ICT platforms. This would empower academic staff to leverage digital tools for both proactive monitoring and transparent reporting.